APLIKASI TEKNIK PENGENDALIAN MUTU PROSES PEMBELAJARAN - Juliani Dyah Trisnawati (Journal of Management and Business, 2003)
This paper will describe about methods or tools for approach of Quality Control, involving functions in educational institution to monitoring, controlling and increasing the effect of Learning Process in Study Program. Technique of Control Chart, Survey of Student, and House of Quality (HOQ) used to justify the methods in one subject as an integrated system.